2020
DOI: 10.3389/fchem.2020.00477
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Synthesis of Oligosiloxanes Mediated by an Air Stable Catalyst, (C6F5)3B(OH2)

Abstract: The utility of (C 6 F 5) 3 B(OH 2) as catalyst for the simple and environmentally benign synthesis of oligosiloxanes directly from hydrosilanes, is reported. This protocol offers several advantages compared to other methods of synthesizing siloxanes, such as mild reaction conditions, low catalyst loading, and a short reaction time with high yields and purity. The considerable H 2 O-tolerance of (C 6 F 5) 3 B(OH 2) promoted a catalytic route to disiloxanes which showed >99% conversion of three tertiary silanes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…[6][7][8][9][10] to their most known function as a temporary protective group for hydroxyl moieties (e.g., natural products synthesis, derivatization, etc.). [11][12][13][14] There are several methods of their synthesis, starting with classical condensation between alcohols and halosilanes, [15] and finishing on catalytic coupling reactions with hydro-, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] vinyl- [33] or allylsilanes, [34,35] and more recently also with silyl formates. [36][37][38] However, in the case of O-silylation of alcohols with alkynylsilanes -this process has never been comprehensively studied, and previous investigations have mainly referred to the problem of C sp -Si bond stability rather than the application of this transformation as an efficient method for obtaining silyl ethers.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] to their most known function as a temporary protective group for hydroxyl moieties (e.g., natural products synthesis, derivatization, etc.). [11][12][13][14] There are several methods of their synthesis, starting with classical condensation between alcohols and halosilanes, [15] and finishing on catalytic coupling reactions with hydro-, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] vinyl- [33] or allylsilanes, [34,35] and more recently also with silyl formates. [36][37][38] However, in the case of O-silylation of alcohols with alkynylsilanes -this process has never been comprehensively studied, and previous investigations have mainly referred to the problem of C sp -Si bond stability rather than the application of this transformation as an efficient method for obtaining silyl ethers.…”
Section: Introductionmentioning
confidence: 99%
“…The Q 3 /(Q 3 + Q 4 ) integral ratio suggested that 2.6% of the Si(OSi) 4 units underwent cleavage, probably due to hydrolysis with a trace of water in the reaction system. 17 The integral ratio of the 29 Si signals of D 2 /(M 1 + D 1 + D 2 ) was 0.91, indicating that the percentage of the condensed silyl groups ( P cond ) was 91% (Table 1). Although the P–R reaction is strongly exothermic, 9 the FT-IR and 29 Si MAS NMR analyses confirmed that the reaction proceeded while retaining the D4R cage structure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experience with polymer chain extension of HSi-telechelic polymers with water did not lead to the formation of cyclics. Under these conditions with low catalyst concentrations (0.02%) (BCF/H 2 O and B(C 6 F 5 ) 3 ∙OH 2 [ 38 ]), redistribution reactions are similarly not efficient. While the reactions here were complete in 30 min, there was no change in the cyclics profile between 30–180 min (SM); redistribution would favor the formation of D 4 which, of the cyclics characterized, was formed in the lowest concentration.…”
Section: Resultsmentioning
confidence: 99%